Understanding the intention of generation Z on Netflix and Viu streaming services - Restu Ayu Mumpuni; Anita Amaliyah; Fasyiah Noor; Indah Laksmiwati; Lukki Lukkitawati (ProTVF, 2021)
Information and Technological sophistication makes consumer preferences’ change. In the past, TV became the only option if you wanted to watch entertainment. Now, various gadgets was available, offering internet-based entertainments. It is a huge market for wide range of products that enable multiple media consumption through combination on both traditional tech forms of media which allows individuals to retain a high level of control in their media use through on-demand media services like Netflix or Viu.This study aims to examine the affect of generation Z attitude and subjective norm to their intention in using streaming services with perspective explained in Theory of Reasoned Action. Generation Z is the generation who is born in the period of 1995 to 2010. The young people of Z generation very familiar with updated technology since their childhood. They used to modern and sophisticated gadgets intensively. Purposive random sampling was applied to collect the data from Diponegoro University’s student (N= 100). Further, quantitative and qualitative methods were invoked to analyze the data. The records of indepth-interview were transcribed and processed using Atlas TI. The results showed that respondents were likely less an intention nor subjectove norm in using streaming service. Thereafter, this study suggests that the content matters play an important role for generation Z in using streaming service, such as Netflix and Viu.